2014
DOI: 10.1186/s13071-014-0518-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anthelmintic activity of medicinal plant extracts and purified condensed tannins against free-living and parasitic stages of Oesophagostomum dentatum

Abstract: BackgroundPlant-derived condensed tannins (CT) show promise as a complementary option to treat gastrointestinal helminth infections, thus reducing reliance on synthetic anthelmintic drugs. Most studies on the anthelmintic effects of CT have been conducted on parasites of ruminant livestock. Oesophagostomum dentatum is an economically important parasite of pigs, as well as serving as a useful laboratory model of helminth parasites due to the ability to culture it in vitro for long periods through several life-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 44 publications
3
58
0
3
Order By: Relevance
“…compound structures) can also modulate the bioactivity. Recent data obtained with GIN models from cattle, small ruminants, and pigs (Novobilský et al, 2011(Novobilský et al, , 2013Quijada et al, 2015;Williams et al, 2014a) lend support to the hypothesis first raised by Molan et al (2003a) that bioactivity is linked to the prodelphinidin/procyanidin (PD/PC) ratio in plants. These recent studies have also revealed that tannin size is an important structural feature that contributes to the extent of the AH effects.…”
Section: Hypotheses On the Modes Of Actionmentioning
confidence: 68%
“…compound structures) can also modulate the bioactivity. Recent data obtained with GIN models from cattle, small ruminants, and pigs (Novobilský et al, 2011(Novobilský et al, , 2013Quijada et al, 2015;Williams et al, 2014a) lend support to the hypothesis first raised by Molan et al (2003a) that bioactivity is linked to the prodelphinidin/procyanidin (PD/PC) ratio in plants. These recent studies have also revealed that tannin size is an important structural feature that contributes to the extent of the AH effects.…”
Section: Hypotheses On the Modes Of Actionmentioning
confidence: 68%
“…An important constraint in the quest for valid tannin data is the requirement for high purity standards for quantitation, which means that the CT concentration and purity of the standards needs to be assessed by CT-specific methods such as thiolysis (Gea et al, 2011;Grabber et al, 2013;Williams et al, 2014a) or nuclear magnetic resonance spectroscopy (Zeller et al, 2015a). We emphasize that the widely used elution of plant extracts with 70% aqueous acetone from Sephadex LH-20 columns for tannin "purification" can lead to CT concentrations as low as ~13 g CTs 100 g −1 "purified sample" (Williams et al, 2014b). Their use would overestimate CT concentrations, so additional steps are required to increase their purity Fryganas, 2016;Brown et al, 2017;Ropiak et al, 2017).…”
Section: Progress In Tannin Analysismentioning
confidence: 99%
“…Condensed tannin (CT) content; mean degree of polymerization (mDP); molar percentages of: procyanidin, cis-flavan-3-ols and galloylation in fractions from various plant materials and estimated effective concentration of CT to reduce C. elegans motility by 50% (EC50). CT 0.45 -1 Note: data are presented for clarity purposes and literature references are provided, F2fraction 2, F3fractions 3; CT content has been reported 37 (calculated with mass response factor calculations); ( a ) data have been corrected for CT content (CT g/100 g of fraction); (n) number of independent experiments (composed of triplicate measurements at each CT concentration treatment); (nd) not detected; (-) not determined. Standard deviation in parentheses.…”
Section: Changes To Cuticle and Sensilla Of Lip Region Observed By Scmentioning
confidence: 99%
“…C. elegans has been used in pharmacological studies of synthetic AH drugs, 31 natural products [32][33][34][35] and even highthroughput screening. 36 Studies on the AH properties of CT against adult GIN are scarce 21,37,38 and culturing of adult C. elegans allowed us to avoid the sacrifice of experimental ruminants or monogastric animals. We screened nematocidal activity of CT in purified fractions derived from model plant materials.…”
Section: Introductionmentioning
confidence: 99%